Diethyldithiocarbamate enhanced chemical generation of volatile palladium species, their characterization by AAS, ICP-MS, TEM and DART-MS and proposed mechanism of action - Vyhnanovský, Jaromír; Kratzer, Jan; Benada, Oldřich; Matoušek, Tomáš; Mester, Zoltán; Sturgeon, Ralph E; Dědina, Jiří; Musil, Stanislav (Analytica chimica acta, 2018)
Comprehensive investigation of chemical generation of volatile species (VSG) of palladium for detection by analytical atomic and mass spectrometry and, specifically, the mechanistic aspects of their formation and tentative identification are presented. VSG was achieved in a flow injection mode using a generator that permitted rapid mixing of acidified sample with NaBH4 reductant. Atomization in a diffusion flame with detection by atomic absorption spectrometry was exclusively used for optimization of generation conditions while inductively coupled plasma mass spectrometry was utilized to investigate overall system efficiency and analytical metrics of the VSG system for potential ultratrace analysis. Sodium diethyldithiocarbamate (DDTC) served as a crucial reaction modifier, enhancing overall system efficiency 9-fold. Combinations of modifiers, Triton X-100 and Antifoam B surfactants provided a synergistic effect to yield a further 2-fold enhancement of VSG. The overall system efficiency was in the range 16-22%, with higher efficiencies correlating with higher Pd concentrations. The contribution of co-generated aerosol to the overall system efficiency, determined by means of concurrent measurement of added Cs, was negligible - less than 0.1%. The nature of the volatile species was investigated using several approaches, but principally by transmission electron microscopy (TEM) after their collection on a grid, and by direct analysis in real time (DART) using high resolution orbitrap mass spectrometry. These experiments suggest a parallel but dual-route mechanism of VSG of Pd, one attributed to generation of a volatile DDTC chelate of Pd and a second to nanoparticle formation.
Keywords: Generation of volatile species; Transmission electron microscopy (TEM); Inductively coupled plasma mass spectrometry; Atomic absorption spectrometry; Palladium; Direct analysis in real time (DART)